Monoclonal gammopathy and serum immunoglobulin levels as prognostic factors in chronic lymphocytic leukaemia. (26th July 2020) - Corbingi, Andrea; Innocenti, Idanna; Tomasso, Annamaria; Pasquale, Raffaella; Visentin, Andrea; Varettoni, Marzia; Flospergher, Elena; Autore, Francesco; Morelli, Francesca; Trentin, Livio; Reda, Gianluigi; Efremov, Dimitar G.; et al.
Summary: The relationship between chronic lymphocytic leukaemia (CLL) and qualitative/quantitative gammaglobulin abnormalities is well established. Nevertheless, in order to better understand this kind of connection, we examined 1505 patients with CLL and divided them into four subgroups on the basis of immunoglobulin (Ig) aberrations at diagnosis. A total of 73 (4·8%), 149 (10%), 200 (13·2%) and 1083 (72%) patients were identified with IgM monoclonal gammopathy (IgM/CLL), IgG monoclonal gammopathy (IgG/CLL), hypogammaglobulinaemia (hypo‐γ) and normal Ig levels (γ‐normal) respectively. IgM paraprotein was significantly associated with a more advanced Binet/Rai stage and del(17p)/ TP53 mutation, while IgG abnormalities correlated with a higher occurrence of trisomy 12. Patients with any type of Ig abnormality had shorter treatment‐free survival (TFS) but no significant impact affecting overall survival (OS) compared to those with normal Ig levels.